HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT TK. III Dr.REKSODIWIRYO PADANG TAHUN 2019 - Idrawati Bahar (Ensiklopedia of Journal, 2020)
Service quality is a measure of how well the service level is delivered according to the patient’s expectations. Patient satisfaction is a feeling happy or upset someone who comes after comparing between perception on performance. Phenomena that occur in RS TK. III Dr. Reksodiwiryo Padang of the data obtained, about 45% of the suggestions and critics that go through the suggestion box and complain directly will complain the healthcare provider’s service to the patient is felt less attention, less communicative in the provision of information with patients and inpatient facilities are less complete. The purpose of this research is to know the quality of service relationships with outpatient satisfaction in RS TK. III Dr. Reksodiwiryo Padang of the year 2019. Type of this research is to design with cross sectional analytic study. This research was conducted on October 2015 – 16December 2019. The population is all of the outpatient in the RS Tk III Dr. Reksodiwiryo totalling 300 men. Samples taken with the technique of accidental sampling amounted to 35 people. The data is processed with the computer then analyzed Univariate and bivariat based on frequency distribution. Research results showed (57,1%) patients declared less satisfied, (62,9%) said the quality of service is not good. There is a meaningful relationship between the quality of service to the satisfaction of the patient. Conclusion the end of more than half of the patients meyatakan were less satisfied. The advice of this research, the hospital is expected to improve the quality of service in order to make the patient's satisfaction.